2009
DOI: 10.1177/0193945909348230
|View full text |Cite
|
Sign up to set email alerts
|

Translating the Pittsburgh Sleep Quality Index Into Arabic

Abstract: This descriptive correlational study describes the translation process and the psychometric testing of the Pittsburgh Sleep Quality Index (PSQI). The PSQI has been successfully translated into Arabic and back-translated into English by 10 Arabic bilingual translators. Then the PSQI is tested in a sample of 35 healthy Arabic bilinguals.The internal consistency reliability for the Global PSQI demonstrates borderline acceptability (Cronbach's alpha = .65). The reliability is further supported by moderate to high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
194
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(202 citation statements)
references
References 37 publications
(87 reference statements)
8
194
0
Order By: Relevance
“…The PSQI has high test-retest reliability and good validity in the psychometric evaluation. [50][51][52] The present study was utilized for the Arabic version of Pittsburgh Sleep Quality Index,which developed by Suleiman et al, [53] using back translation technique and psychometrically tested in different studies [53,54] which confirmed its validity and reliability for measuring sleep disturbances among Arabic clinical population.…”
Section: Tool and Data Collection Proceduresmentioning
confidence: 54%
“…The PSQI has high test-retest reliability and good validity in the psychometric evaluation. [50][51][52] The present study was utilized for the Arabic version of Pittsburgh Sleep Quality Index,which developed by Suleiman et al, [53] using back translation technique and psychometrically tested in different studies [53,54] which confirmed its validity and reliability for measuring sleep disturbances among Arabic clinical population.…”
Section: Tool and Data Collection Proceduresmentioning
confidence: 54%
“…24,58 However, it is important to note the borderline internal consistency reliability (α = .65) of the PSQI measure. Even though similar alpha levels (e.g., α = .65-.69) have recently been reported for the PSQI in other published studies 78,79 and an alpha of .65 is considered “minimally acceptable”, 80 it is nonetheless important to interpret findings with this in mind. Finally, even though high levels of stress are the strongest predictor of poor sleep quality among college students, 7 no measures of negative affect or stress were included in this study.…”
Section: Commentmentioning
confidence: 61%
“…Poor sleep quality may be due to physical illness, side effects of medications, psychiatric disorders (such as depression, anxiety disorder, insomnia, schizophrenia), or use of psychoactive substances [3][4][5][6]. Poor sleep quality and sleep disturbances can adversely impact quality of life by reducing productivity at the workplace and by making social activities less enjoyable [3]. Thus, assessment of sleep quality is important for a wide range of clinical and behavioral research and for practitioners of medicine and psychology.…”
Section: Introductionmentioning
confidence: 99%